2024
DOI: 10.3390/biomedicines12030554
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Adenylate Energetics Is Related to Endothelial and Microvascular Function in Long COVID

Marzena Romanowska-Kocejko,
Agata Jędrzejewska,
Alicja Braczko
et al.

Abstract: Adenine nucleotides play a critical role in maintaining essential functions of red blood cells (RBCs), including energy metabolism, redox status, shape fluctuations and RBC-dependent endothelial and microvascular functions. Recently, it has been shown that infection with the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) might lead to morphological and metabolic alterations in erythrocytes in both mild and severe cases of coronavirus disease (COVID-19). However, little is known about the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…A new diagnostic technique named Flow-Mediated Skin Fluorescence (FMSF), which enables a noninvasive evaluation of the vascular circulation and metabolic regulation, was introduced in 2017 [ 17 , 18 , 19 , 20 , 21 ]. The FMSF technique is based on monitoring the intensity of nicotinamide adenine dinucleotide (NADH) fluorescence from skin tissue on the forearm in response to blocking and releasing blood flow as a function of time.…”
Section: Introductionmentioning
confidence: 99%
“…A new diagnostic technique named Flow-Mediated Skin Fluorescence (FMSF), which enables a noninvasive evaluation of the vascular circulation and metabolic regulation, was introduced in 2017 [ 17 , 18 , 19 , 20 , 21 ]. The FMSF technique is based on monitoring the intensity of nicotinamide adenine dinucleotide (NADH) fluorescence from skin tissue on the forearm in response to blocking and releasing blood flow as a function of time.…”
Section: Introductionmentioning
confidence: 99%
“…In this last section, the remaining papers are summarized. Romanowska-Kocejko et al observed that the dysregulation of metabolic processes in erythrocytes, in addition to endothelial and microvascular dysfunction, is associated with the decreased delivery of intracellular oxygen in patients with post-COVID-19 condition [ 36 ]. In accordance with the hypothesized endothelial problems, another study published in this Special Issue found that pulmonary embolism, as well as the use of a high-flow nasal cannula and prolonged hospitalization, is associated with reduced functional capacity and a higher likelihood of exertional desaturation in patients with post-COVID-19 condition [ 37 ].…”
mentioning
confidence: 99%
“…In accordance with the hypothesized endothelial problems, another study published in this Special Issue found that pulmonary embolism, as well as the use of a high-flow nasal cannula and prolonged hospitalization, is associated with reduced functional capacity and a higher likelihood of exertional desaturation in patients with post-COVID-19 condition [ 37 ]. Thus, the association of endothelial and microvascular dysfunction with reduced intracellular oxygen delivery may partly explain this post-COVID fatigue and limited functional capacity [ 36 ]. Similarly, the endothelial disfunction of the brain would explain the presence of post-COVID cognitive symptomatology [ 38 ].…”
mentioning
confidence: 99%